Heme oxygenase-1 as a therapeutic target in inflammatory disorders of the gastrointestinal tract - Vijayan, Vijith; Mueller, Sebastian; Baumgart-Vogt, Eveline; Immenschuh, Stephan (World journal of gastroenterology, 2010)
Heme oxygenase (HO)-1 is the inducible isoform of the first and rate-limiting enzyme of heme degradation. HO-1 not only protects against oxidative stress and apoptosis, but has received a great deal of attention in recent years because of its potent anti-inflammatory functions. Studies with HO-1 knockout animal models have led to major advances in the understanding of how HO-1 might regulate inflammatory immune responses, although little is known on the underlying mechanisms. Due to its beneficial effects the targeted induction of this enzyme is considered to have major therapeutic potential for the treatment of inflammatory disorders. This review discusses current knowledge on the mechanisms that mediate anti-inflammatory protection by HO-1. More specifically, the article deals with the role of HO-1 in the pathophysiology of viral hepatitis, inflammatory bowel disease, and pancreatitis. The effects of specific HO-1 modulation as a potential therapeutic strategy in experimental cell culture and animal models of these gastrointestinal disorders are summarized. In conclusion, targeted regulation of HO-1 holds major promise for future clinical interventions in inflammatory diseases of the gastrointestinal tract.